Identificación de los tipos de injertación aplicados en el cultivo Cacao (Theobroma cacao L.) en el trópico ecuatoriano. - Alvarado Pacheco, Darlington Axcel (2022)
This document presents Identification of grafting methods applied in the cultivation of Theobroma cacao L. in the Ecuadorian tropics. Which is sought with the identification of these grafting methods as we can say or because cocoa grafting is a method of vegetative or asexual reproduction that consists of grafting a branch or part of it (a stem) on a rootstock propagated by seeds. , so that the stem or stem is in close contact with the rootstock. The objectives were to determine the best methods for grafting, and the growth promoter with its relationship, to establish a protocol that allows greater efficiency in obtaining graft clones and the Cost / Benefit relationships of the applied treatments, It allows to establish in a short time a commercial plantation. In itself it is sought and allows to renew these native plants. It allows to reproduce fruit trees with high productivity and fruit quality. It allows to standardize or homogenize the time of fruit production. The grafting process (buds or tines), is practical and easy to implement, which allows obtaining plants with high production and health, similar to the parent plant (mother), it is recommended to use selected material on the farms, adapted to these conditions, seeks to make them more resistant and very beneficial plants for farmers